PROBLEMA PENGEMBANGAN IPTEK DI INDONESIA - Thohari, Thohari (Jurnal Bestari, 1991)
The Development of science and technology is the most crucial problems to develop Indonesia. This, However, will not sail away to the "ideal end" unless Indonesian people develop their skill and capacity. Most of modern countries are alwaysconsist of skillfull people characterized by : creativity, dynamic, effectiveness, efficiency and productivity. The development of indonesia hereby depends on it's human resources.